Swans of the 70s: The First Women of the South African Navy’s Permanent Force - Steyn, Leon (Scientia Militaria - South African Journal of Military Studies, 2023)
The service of women in the South African Navy and its predecessors can be divided into three distinct historical periods. Firstly, there was the service of the so-called Swans with the South African Naval Forces during the Second World War, followed by the service of women in the Navy’s Permanent Force from 1972 with the South African Defence Force, and lastly, their employment in the Navy since 1994 when a new democratic dispensation saw the establishment of the South African National Defence Force. While the first and last eras mentioned above have received a good measure of attention in academic writing, the second has not.This article attempts to provide much-needed focus on a neglected but important era in our naval history. It details the first permanent appointment of women in the South African Navy in 1972 and 1973, which marked the departure point of women’s service in a permanent capacity – an important groundbreaking event that would lead to expanded utilisation in later years. The article discusses their experiences, particularly their utilisation and challenges to integrate into a male-dominated Navy during the early and mid-1970s.The research methodology employed for the study on which this article is based, combined the traditional “top-down” (archival sources) and grassroots “from the bottom-up” (oral history) approaches. This method offered a balanced and corroborated view of these important trailblazing events that occurred 50 years ago.